Pengaruh Pemberian Intervensi Pernafasan Purshed Lip Breathing pada Pasien PPOK di Ruang Kelas 3 RS Bhayangkara Bandar Lampung - Febri Sasmita; Giri Susanto (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT The number of people with COPD in Indonesia is 4.8 million with a prevalence of 5.6%, this number will continue to increase along with the growth of smokers and poor air quality in the Indonesian region. COPD is a narrowing or blockage of the airway that causes limited airflow to the lungs. Problems often experienced by patients with COPD are coughing up phlegm and shortness of breath. Pursed lips breathing exercise is an effective breathing control exercise program that is applied to regulate and improve breath frequency patterns, improve oxygenation fulfilment. The writing of this scientific work aims to carry out nursing care for COPD patients with pursed lip breathing interventions in Classroom 3 of Bhayangkara Police Hospital Lampung. Methods of writing In this scientific paper the author uses a nursing care approach that focuses on nursing actions, the nursing action chosen is the provision of pursed lip breathing therapy in COPD patients. Nursing care focused on nursing actions was carried out in October 2024 at Bayangkara Police Hospital Lampung. Data collection using informed consent physical examination tools and KMB assessment format, and ethical principles in making this scientific paper is the principle of nursing ethics. The evaluation results obtained were that the nursing problems that arose on the subject of ineffective airway care showed improvement. The results of the patient showed improvement with shortness and coughing phlegm reduced and from the results of SPO2 90% to SPO2 97% while patient 2 showed improvement in shortness and coughing phlegm from the results of spo2 92% to SPO2 99%. It can be concluded that there is an increase in SPO2 in COPD patients after being given pursed lip breathing therapy. Keywords: PPOK, Pursed Lip Breathing.  ABSTRAK PPOK merupakan penyempitan atau penyumbatan jalan napas dan  Masalah yang sering dialami pasien adalah batuk berdahak dan sesak nafas. Salah satu cara menanganinya dengan Latihan pernapasan pursed lips breathing yang efektif diterapkan untuk mengatur dan memperbaiki pola frekuensi napas, meningkatkan pemenuhan oksigenasi.Tujuan dari studi kasus ini adalah untuk Melakukan Asuhan Keperawatan Pada Pasien  PPOK dengan intervensi pursed lip breathing di Ruang Kelas 3 RS Bhayangkara Polda Lampung. Metode yang digunakan berupa Deskriptif dengan pendekatan studi kasus mengenai penerapan pursed lip breathing Pada Pasien  PPOK. Populasi dalam studi kasus ini adalah pasien PPOK sebanyak 2 pasien. Kegiatan studi kasus ini dilaksanakan pada Oktober 2024. Intervensi yang diberikan adalah pursed lip breathing. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan menggunakan lembar observasi pemeriksaan kapasitas fungsional paru, format pengkajian dan alat pengukur saturasi oksigen (oxymetri). Hasil evaluasi yang diperoleh yaitu masalah keperawatan yang muncul pada subyek asuhan bersihan jalan napas tidak efektif  menunjukkan perbaikan. Dengan hasil pasien menunjukkan perbaikan dengan sesak dan batuk berdahak berkurang dan dari hasil SPO2 90% ke SPO2 97% sedangkan pada pasien 2 menunjukkan perbaikan sesak dan batuk berdahak dari hasil spo2 92% ke SPO2 99%. Dapat disimpulkan terdapat peningkatan SPO2 pada pasien PPOK setelah diberikan terapi pursed lip breathing. Kata Kunci: PPOK, Pursed Lip Breathing